Advancement in design and failure analysis of aluminium foam-filled honeycomb crash absorbers - Valente, Goncalo; Ghasemnejad, Hessam; Srimanosaowapak, S.; Watson, James W. (Springer, 2023)
Honeycomb structures are frequently used as energy absorption devices in the automotive and aerospace industry. Many studies have been conducted to optimise these structures and improve crashworthiness behaviour. This paper attempts to improve the crashworthiness behaviour of a honeycomb crash box by filling the cells with open-cell aluminium foams. Experimental tests were conducted to develop the honeycomb and aluminium foam material model and, also, to validate the finite element model by experimental data. The finite element model was developed in ABAQUS, and different variables were parameterised to aim a quick implementation. The empty aluminium honeycomb crash box is used as a term of comparison with the foam-filled ones. Foam-filling the crash box allows the control of the densification zone for different impact energies using open-cell aluminium foam, which shows the main novelty of this research. In the end, the optimised structure is presented concerning the optimum number of foam-filled cells and, also, to the aluminium foam’s density that best fits this application.
Keywords: aluminium honeycomb; aluminium foam; impact; FEM; optimisation